Linkage between scientific community and enterprises in national innovation system - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Linkage between scientific community and enterprises are found as important matters of nations, particularly in contexts of strong impacts from the 4-th Industrial Revoluation. The latter requires countries to get rich knowledge capitals to set up solid platforms for national development. The knowledge capitals get formed, develop and stored mostly in scientific communities. In the new era, numerous enterprises have passed strong development stages and own large economic groups with enriched capacities and potentials including knowledge capitals. But not every enterprise can do it since majority of enterprises are difficult in developing knowledge capitals, both quantitativeky and qualitatively. Linkage with scientific community through training activities, tranfer of research results, joint efforts for production and commercialization of research results are found among important solutions to assist enterprises fast to get new knowledge for application in innovation activities, production and business operations. Herfe, the State plays very important roles in completting the national innovation systems (NISs) to offer eco-environments to develop the linkage between scientific communities and enterprises which are important pillars for national economy. Code: 19071001